2020
DOI: 10.1002/jts.22600
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Anxiety During the COVID‐19 Pandemic in an Urban, Low‐Income Public University Sample

Abstract: Mental health disparities in the aftermath of national disasters and the protective role of socioeconomic status are both well documented. We assessed the prevalence of depression and anxiety symptoms among underresourced public university students during the COVID‐19 pandemic in New York City. Between April 8, 2020, and May 2, 2020, adult students ( N = 1,821) across the CUNY system completed an online survey examining COVID‐19–related stressors and mental health and sociodemographic fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

30
218
6
15

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 222 publications
(269 citation statements)
references
References 65 publications
30
218
6
15
Order By: Relevance
“…10 Multiple stressors contributed to the increased distress, including worry about their own health and of their loved ones (91%), difficulty concentrating (89%), disruptions to sleep patterns (86%), decreased social interactions due to physical distancing (86%), and increased concerns of academic performance (82%). Surveys conducted between April and May 2020 with students sampled from Southwest 11 and Northeast U.S. universities [12][13][14] have revealed similar findings.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…10 Multiple stressors contributed to the increased distress, including worry about their own health and of their loved ones (91%), difficulty concentrating (89%), disruptions to sleep patterns (86%), decreased social interactions due to physical distancing (86%), and increased concerns of academic performance (82%). Surveys conducted between April and May 2020 with students sampled from Southwest 11 and Northeast U.S. universities [12][13][14] have revealed similar findings.…”
mentioning
confidence: 63%
“…[5][6][7][8] Evidence accumulated thus far reveals that the COVID-19 pandemic has resulted in considerable psychological distress across the general population, including increased stress, anxiety, and depression, 9 and preliminary data suggests that college students may be experiencing even higher rates of psychological distress. [10][11][12][13][14] Indeed, one study found that 71% of students (N ¼ 195) sampled from a large U.S. university reported increased stress and anxiety due to the COVID-19 outbreak. 10 Multiple stressors contributed to the increased distress, including worry about their own health and of their loved ones (91%), difficulty concentrating (89%), disruptions to sleep patterns (86%), decreased social interactions due to physical distancing (86%), and increased concerns of academic performance (82%).…”
mentioning
confidence: 99%
“…Reasons postulated are lower education, precarious jobs and lower household and intergenerational wealth accumulation. 6 , 8 , 10 , 18–22 Younger age may play a special role as individuals are just starting with their career and adult lives. A March 2020 study of 6666 US adults found that younger age was associated with perceiving a higher risk of getting quarantined, running out of money and depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“… 20 , 21 Families with children and lower incomes are susceptible to greater stress leading to depression and anxiety due to multiple social and economic stressors that have been accentuated by the pandemic. 18–22 Sociocultural factors from before the pandemic, along with the vulnerability to COVID-19, have rendered catastrophic consequences for several such groups (young, urban, minorities and families with low incomes). 18–21 Unfortunately, these are the groups that traditionally had the lowest access to quality mental healthcare even before the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation